Answer:
shhhhhhhhhhhhhhhhhh
Step-by-step explanation:
do it yurself lol
Answer:
Option 2 - ![x=\frac{7\pm3\sqrt{3}i}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B7%5Cpm3%5Csqrt%7B3%7Di%7D%7B2%7D)
Step-by-step explanation:
Given : Equation ![(x-5)^2+3(x-5)+9=0](https://tex.z-dn.net/?f=%28x-5%29%5E2%2B3%28x-5%29%2B9%3D0)
To find : What is the solution of the equation ?
Solution :
Using substitution method,
Let y=x-5
![y^2+3y+9=0](https://tex.z-dn.net/?f=y%5E2%2B3y%2B9%3D0)
Using quadratic formula, ![x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
Here, a=1, b=3 and c=9
![y=\frac{-3\pm\sqrt{3^2-4(1)(9)}}{2(1)}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-3%5Cpm%5Csqrt%7B3%5E2-4%281%29%289%29%7D%7D%7B2%281%29%7D)
![y=\frac{-3\pm\sqrt{-27}}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-3%5Cpm%5Csqrt%7B-27%7D%7D%7B2%7D)
![y=\frac{-3\pm3\sqrt{3}i}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-3%5Cpm3%5Csqrt%7B3%7Di%7D%7B2%7D)
Substitute back,
![x=\frac{-3\pm3\sqrt{3}i}{2}+5](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-3%5Cpm3%5Csqrt%7B3%7Di%7D%7B2%7D%2B5)
![x=\frac{-3\pm3\sqrt{3}i+10}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-3%5Cpm3%5Csqrt%7B3%7Di%2B10%7D%7B2%7D)
![x=\frac{7\pm3\sqrt{3}i}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B7%5Cpm3%5Csqrt%7B3%7Di%7D%7B2%7D)
Therefore, option 2 is correct.
Answer:
i and iii
Step-by-step explanation:
Answer: x^#22
Step-by-step explanation: Cancel the common factor of
x^56 and x^24.
So your answer is x^32 I’m trying my best to explain the answer.
A because 3 is rational, and it’s a natural and whole number because it’s about 0. It’s an integer because integers include negative and positive numbers.